Adopting blended learning: An analysis and review of students' acceptance in UiTM Pahang / Azniza Ahmad Zaini, Fazlin Marini and Roger Canda - Ahmad Zaini, Azniza; Marini, Fazlin; Canda, Roger (2013)
This paper discusses the findings of an empirical study in adopting Blended Learning (BL) approach for teaching diploma students in Universiti Teknologi MARA (UiTM) Pahang. Self-administered questionnaires were distributed to 86 final year students of Diploma in Computer Science registered for the programming course and 67 students of Diploma in Banking registered for the Malaysian economy course to assess their acceptance towards the new approach. The students' perception on i-Learn Portal usage for BL approach as well as the benefits of implementing Blended Learning approach in their learning process were also identified. The findings reveal that the students could adapt with the BL approach since most of the students are computer and Internet literate and gradually adapting to the mixed approaches of assessments. The findings also show that most of the students agreed that the implementation of Blended Learning should be continued corresponding with the development of technology, but there are some suggestions on improvement of the Learning Management System (LMS) portal to achieve the benefits that Blended Learning offers either in physical or virtual classrooms.